HISTOLOGICAL STUDIES OF THE BUFFALO ADENOHYPOPHYSIS WITH REFERENCE TO PHASES OF ESTRUS CYCLE - N. Akhtar; G. Nabi; L.A. Lodhi; S. Ali; N. Ahmad; S. U. Rahman; M. Akhtar (Journal of Animal and Plant Sciences, 2012)
To study the histological details of the buffalo adenohypophysis responsible for the production of gonadotropin hormones, 60 healthy and non pregnant buffaloes brought to Faisalabad abattoir were selected. These buffaloes were divided into three groups according to their age, viz. group A= buffalo heifers, group B= buffaloes in lactation 1-3 and group C = buffaloes in lactation 4th or above. These buffaloes were in their estrus, anestrus or diestrus phase. The reproductive tracts of these buffaloes were examined to confirm their stage of estrus cycle. Pituitary glands of selected buffaloes were collected immediately after slaughter. These pituitary glands were round in shape and light pink in colour. Mean length, width and thickness of the pituitaries collected from heifers during anestrus, estrus and diestrus phases showed non-significant differences among them in respect of size and colour. Mean weight of the pituitaries (305±7.5 and 300±7.5 mg) collected from buffaloes of group A and B which were in estrus phase was significantly (P<0.05) higher than 270±7.5mg found for buffaloes in group C, and was also significantly (P<0.05) higher than for buffaloes of all groups which were in their estrus and diestrus phases. Histological staining procedure i.e. Azan Mallory Heidenhain or Hematoxylin and Eosin stains were used to stain the cut sections of buffalo adenohypophysis. Gonadotrophs population (19.66%) recorded for buffaloes in lactation 1-3 was significantly (P<0.05) higher than 14.75 and 13.75% found in adenohypophysis of heifers and buffaloes in lactation 4 th or above. Number of maturing (6-10 mm) GF (104) found on the ovaries of heifers was significantly (P<0.05) higher than 40 and 15 found for buffaloes in lactation 1-3 and buffaloes in lactation 4 th or above. It was concluded that heifers and buffaloes in lactation 1-3 during estrus showed significantly higher gonadotrophs population than buffaloes in lactation 4th or above, indicating higher ovarian activity in young animals.
Keywords: Buffalo; Adenohypophysis; Estrus phases; Gonadotrophs